Correlation of Site and Size of Tympanic Membrane Perforation and Middle Ear Air Space Volume with Magnitude of Hearing Loss - Virk, Ramandeep Singh; Kudawla, Krishan; Bansal, Sandeep; Rathod, Ramya; Behera, Samarendra (Annals of Otology and Neurotology, 2019)
Introduction The effects of tympanic membrane perforations on middle ear sound transmission are not well characterized, largely because ears with perforations typically have additional pathological changes. It has been established that the larger the perforation, the greater is the hearing loss (HL).Aim This study aimed to correlate the location and size of tympanic membrane perforation and middle ear air space volume with the magnitude of HL in patients with tubotympanic or inactive mucosal type of chronic otitis media (COM).Materials and Methods A prospective clinical study of patients with tympanic membrane perforations due to COM and without any other ear disease and who attended the Otolaryngology services at our institute between July 2010 and December 2011 was conducted. A total of 300 ears were evaluated by performing otoendoscopy, followed by photo documentation and audiological investigations (pure-tone audiometry and tympanometry). Tympanic membrane perforations were categorized based on their size and location, and the mean air-bone (AB) gap between the various types of perforations was compared and statistically analyzed with significance level of p < 0.05.Results Out of 300 ears, maximum number of ears (n = 124, 41.3%) had large-sized perforations (> 30 mm2) that had a maximum mean AB gap of 26.43 dB, and minimum number of ears (n = 60, 20%) had small-sized perforations (0–9 mm2) that had minimum mean AB gap of 9.12 dB. The remaining were medium-sized perforations that had mean AB gap of 16.13 dB. Depending on the location, maximum were central perforations (n = 198, 66%) and minimum were anterosuperior (AS) perforations (n = 9, 3%). Based on the middle ear volume on tympanometry, maximum ears were of low-volume group (n = 246, 92%) that had larger mean AB gap of 19.96 dB HL when compared with the high-volume group (n = 24, 8%) with 11.80 dB HL. AB gap was maximum at lower frequencies and decreased with increase in frequencies except at 4,000 Hz, that is, 56.9 dB HL at 250 Hz, 42.6 at 500 Hz, 41.5 at 1,000 Hz, 32.4 at 2,000 Hz, and 49.5 at 4,000 Hz.Conclusion HL increases as the area of tympanic membrane perforation increases. There is an inverse relationship between HL and middle ear air space volume. Comparing the small-sized perforations at different sites with the middle ear volume being low, it was found that posterosuperior (PS) perforations had 4 to 7 dB greater HL than AS and anteroinferior (AI). However, the relationship was statistically insignificant. The phase cancellation effect of round window causing greater HL in posteroinferior (PI) perforations does not exist in small- and medium-sized perforations. HL is greater at lower frequencies and less at higher frequencies.
Keywords: air-bone gap; chronic otitis media; various sites and sizes of perforation